2021
DOI: 10.1002/saj2.20355
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of on‐farm soil health scores with corn and soybean yield in the midwestern United States

Abstract: Soil health assessments are interpretive frameworks that estimate a soil's health by scoring various soil biological, chemical, and physical attributes to guide soil and crop management. Few large-scale analyses of soil health assessment scores exist. Thus, our objectives were to (a) summarize soil health scores at farms across much of the midwestern United States, (b) evaluate how individual soil health indicators influence assessment composite scores, (c) assess correlations among composite scores, and (d) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…(2018) similarly found that CC led to increases in soil water infiltration and soybean yield by 80 and 14%, respectively, compared with no‐CC. Even though the interpretation of yield and soil health relationships are soil property and location specific, several studies have suggested that CC adoption can improve the soil fertility, structure, and hydrothermal properties while increasing cash crop yield stability (Crookston et al., 2021; Fontana et al., 2021; Williams et al., 2018). Although the relationship was not more definitive in our analysis, linking soil health relative to a reference state with yield outcomes is an active area of research that deserves more attention in the development of soil health assessments on farms (Wood & Blankinship, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) similarly found that CC led to increases in soil water infiltration and soybean yield by 80 and 14%, respectively, compared with no‐CC. Even though the interpretation of yield and soil health relationships are soil property and location specific, several studies have suggested that CC adoption can improve the soil fertility, structure, and hydrothermal properties while increasing cash crop yield stability (Crookston et al., 2021; Fontana et al., 2021; Williams et al., 2018). Although the relationship was not more definitive in our analysis, linking soil health relative to a reference state with yield outcomes is an active area of research that deserves more attention in the development of soil health assessments on farms (Wood & Blankinship, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…similarly found that CC led to increases in soil water infiltration and soybean yield by 80 and 14%, respectively, compared with no-CC. Even though the interpretation of yield and soil health relationships are soil property and location specific, several studies have suggested that CC adoption can improve the soil fertility, structure, and hydrothermal properties while increasing cash crop yield stability(Crookston et al, 2021;Fontana…”
mentioning
confidence: 99%
“…Cultivated land system health assessment is an explanatory framework that evaluates the health condition of cultivated land systems by scoring the biological, chemical, and physical aspects of cultivated land in order to guide cultivated land utilization and crop production management [ 71 ]. The significance of the cultivated land health evaluation index at different scales is dynamic and must vary as index properties and resource management objectives for cultivated land change.…”
Section: Discussionmentioning
confidence: 99%
“…This is an exciting development, but it is concerning that they found poor correlations with most of the other soil health tests currently available. Others have found similarly poor correlations with yield, but important relationships with other soil parameters (Crookston et al, 2022(Crookston et al, , 2023Rogers et al, 2018). This does not mean it is the end, but rather it is the beginning of a long road of research and practical application working cooperatively together to improve production and sustainability.…”
Section: Soil Testingmentioning
confidence: 99%